NOVEL HAYY IBN YAQDZAN KARYA IBN THUFAIL DAN NOVEL TARZAN OF THE APES KARYA EDGAR RICE BURROUGH (ANALISIS KOMPARATIF STRUKTUR NARATIF) - Fathi Hidayah; Muhammad Endy Fadlullah (INCARE, International Journal of Educational Resources, 2021)
The novel is a description of the author's experiences, points of view and ideas which are set in a series of stories. The idea of ​​a novel is a representation of the picture of human life. Hayy bin Yaqdzan and Tarzan of The Apes are two novels that have a similar story. To find out the extent to which these two literary works are similar, a narrative structure analysis of the two novels is carried out. This study aims to compare the narrative structure of the novels Hayy bin Yaqdzan by Ibnu Thufail and Tarzan of The Apes by Edgar Rice Burrogh. This type of research uses literature study, novel as the material object of research. The narrative structure analysis uses the Badr-Stanton model by analyzing the themes, characterizations, plot and setting of the novel. Comparative analysis using content analysis of each novel narrative structure. The result is the narrative structure of Hayy bin Yaqzhan novel has similirities with Tarzan of The Apes within themes, characterization, plot and settting.